The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s1010-7940(02)00110-0
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone metabolism in pediatric cardiac patients treated by continuous povidone–iodine irrigation for deep sternal wound infection

Abstract: Our data showed that the use of povidone-iodine irrigation in the patients with DSWI has not lead to any significant alteration in thyroid function within the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…22,23 Based on these findings, a history of iodine exposure is an important risk factor for the delayed elevation of TSH, but the susceptibility to iodine excess differs from person to person. 24 In our study, some infants showed high urinary iodine excretion. Fuse 25 reported that the computed median value of urinary iodine concentration was 281AE6 lg/l, and extremely high values exceeding 1000 lg/l were found in 16% of schoolchildren.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…22,23 Based on these findings, a history of iodine exposure is an important risk factor for the delayed elevation of TSH, but the susceptibility to iodine excess differs from person to person. 24 In our study, some infants showed high urinary iodine excretion. Fuse 25 reported that the computed median value of urinary iodine concentration was 281AE6 lg/l, and extremely high values exceeding 1000 lg/l were found in 16% of schoolchildren.…”
Section: Discussionsupporting
confidence: 49%
“…In contrast, iodine excess is considered more problematic for the thyroid function of preterm infants because they are susceptible to excessive administration of iodine via radiographic contrast agents and disinfectant agents 22,23 . Based on these findings, a history of iodine exposure is an important risk factor for the delayed elevation of TSH, but the susceptibility to iodine excess differs from person to person 24 . In our study, some infants showed high urinary iodine excretion.…”
Section: Discussionmentioning
confidence: 55%
“…Presently, concentrations of topical PVP-I solutions vary substantially according to the operative procedure, ranging up to 10 % in visceral and urologic surgery [17,18]. The topical administration of PVP-I must be used with caution, particularly in patients with previous hypersensitivity reactions against iodine, impaired thyroid or renal function, and following burn injuries [19,20]. For many decades, the natural element iodine has been recognised to possess antiseptic properties with a universal spectrum being effective against gram+ and gram-bacteria, mycobacteria, bacterial spores, fungi, viruses, and protozoa [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, one developed severe primary hypothyroidism requiring treatment, the second resolved after transient treatment, and the third resolved spontaneously (23). Other studies have shown that the use of povidone-iodine irrigation in association with delayed sternal closure did not lead to any significant alteration in thyroid function (2426). Further studies are needed to assess the need for monitoring thyroid function after cardiac angiography or prolonged exposure to iodine-containing antiseptics.…”
Section: Iodine-induced Hypothyroidismmentioning
confidence: 93%